A interpretação de Mário Pedrosa sobre a revolução de 1930 e o golpe de 1964 - Vilas Boas, Josnei Di Carlo (2013)
This dissertation aims to grasp the interpretation of Mario Pedrosa (1900-1981) about the Revolution of 1930 and the Coup of 1964 and understand its orientation to political action in opposition to the regime established by Getulio Vargas in the thirties and the Army in sixty. In order to achieve the proposed objectives, this research focuses on two moments of intellectual production of Pedrosa, the essay Esboço de uma análise da situação econômica e social do Brasil, drafted with Livio Xavier during the Revolution of 1930, and the books A opção imperialista and A opção brasileira, whose writing started soon after the Coup of 1964.